2020
DOI: 10.3390/coatings10101007
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and Antibacterial Activity of a Plasma-Sprayed CeO2 Coating on a Titanium (Ti)-Based Dental Implant

Abstract: Peri-implantitis, often induced by oral pathogens, is one of the main reasons for the clinical failure of dental implants. The aim of this study was to investigate the biocompatibility, osteogeneic, and antibacterial properties of a cerium oxide (CeO2) coating containing high proportions of Ce4+ valences on a titanium-based dental implant biomaterial, Ti-6Al-4V. MC3T3-E1 cells or bone marrow stem cells (BMSCs) were seeded onto Ti-6Al-4V disks with or without CeO2 coating. Compared to the control, the plasma-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Graphene-chitosan hybrid dental implants were reported to promote osteoblast proliferation while reducing biofilm formation and bacterial activity [ 15 ]. Similar observations were also reported for titanium implants treated with zinc-containing tricalcium phosphate (Zn-TCP), poly-ε-caprolactone/titania (PCL/TiO 2 ), or plasma-sprayed cerium oxide (CeO 2 ) [ 16 , 17 , 18 , 19 ]. Other titanium implant-coating materials, such as nano-Ag and poly-ethylene oxide (PEO), possess notable antibacterial properties [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 71%
“…Graphene-chitosan hybrid dental implants were reported to promote osteoblast proliferation while reducing biofilm formation and bacterial activity [ 15 ]. Similar observations were also reported for titanium implants treated with zinc-containing tricalcium phosphate (Zn-TCP), poly-ε-caprolactone/titania (PCL/TiO 2 ), or plasma-sprayed cerium oxide (CeO 2 ) [ 16 , 17 , 18 , 19 ]. Other titanium implant-coating materials, such as nano-Ag and poly-ethylene oxide (PEO), possess notable antibacterial properties [ 20 , 21 ].…”
Section: Introductionsupporting
confidence: 71%
“…Processing of titanium and its alloys has been done through several approaches. These include, but are not limited to, new alloy formation, laser or UV treatment, antimicrobial peptides, plasma spraying, anodization, silanization, antimicrobial coatings, and photolithography. , Most of these studies have reported comparisons of the attachment behavior of multiple species on the modified and control surfaces. The bacterial species tested in several studies have been categorized under the yellow (early), orange (intermediate), or red complexes (late colonizers), Table .…”
Section: In Vitro In Vivo and Clinical Studies Of Titanium Dental Imp...mentioning
confidence: 99%
“…Surface modification techniques adopted for metals and alloys can be mechanical (grinding, polishing, blasting), chemical (alkali/acid treatment, anodization), or physical (spraying, PVD). ,, These surface modification approaches are mainly aimed at making the implant surface more rough and porous. Enhanced surface roughness as well as the porous nature of the implant will lead to enriched protein adsorption that promotes better cell adhesion and their ingrowth into the porous layers of the surface. , A bioactive surface with a porous nanonetwork structure can be generated onto a Ti/Ti alloy-based implant by a simple alkaline treatment with a high concentration of NaOH. It is also reported that elements with antimicrobial properties (Ag, Zn, Ce, etc. ), as well as enhancement of osseointegration (Ca, Mg, Zr, Se, Ce etc.…”
Section: Introductionmentioning
confidence: 99%
“…), as well as enhancement of osseointegration (Ca, Mg, Zr, Se, Ce etc. ), can be incorporated into the thus-formed nanonetwork structure by subsequent treatment with a respective elemental solution. ,,, These elements will be decorated over the nanonetwork structure over the surface to promote biocompatibility and add biofunctions to the Ti/Ti alloy-based implants. A similar approach for the incorporation of beneficial elements such as Ag, Zn, Ca, and Sr to Ti/Ti alloys was attempted by our research group, and it resulted in an implant with enhanced surface properties with good biocompatibility, which will help fasten the healing process. ,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation